Reconfigurable Digital Metamaterial for Dynamic Switching of Terahertz Anisotropy - Pitchappa, Prakash (2017)
A microelectromechanically reconfigurable digital metamaterial for dynamic switching of terahertz anisotropy is experimentally demonstrated. Out-of-plane reconfigurable microcantilevers placed in orthogonal direction with isolated control allows active making and breaking of unit cell symmetry. The electrical control, miniaturized size, and ease of process integration make the reported microelectromechanical system metamaterial ideal for the realization of THz polarimetric devices.